Leptin's role in lipodystrophic and nonlipodystrophic insulin-resistant and diabetic individuals. - Moon, Hyun-Seuk; Dalamaga, Maria; Kim, Sang-Yong; Polyzos, Stergios A; Hamnvik, Ole-Petter; Magkos, Faidon; Paruthi, Jason; Mantzoros, Christos S (Endocr Rev, 2013)
Leptin is an adipocyte-secreted hormone that has been proposed to regulate energy homeostasis as well as metabolic, reproductive, neuroendocrine, and immune functions. In the context of open-label uncontrolled studies, leptin administration has demonstrated insulin-sensitizing effects in patients with congenital lipodystrophy associated with relative leptin deficiency. Leptin administration has also been shown to decrease central fat mass and improve insulin sensitivity and fasting insulin and glucose levels in HIV-infected patients with highly active antiretroviral therapy (HAART)-induced lipodystrophy, insulin resistance, and leptin deficiency. On the contrary, the effects of leptin treatment in leptin-replete or hyperleptinemic obese individuals with glucose intolerance and diabetes mellitus have been minimal or null, presumably due to leptin tolerance or resistance that impairs leptin action. Similarly, experimental evidence suggests a null or a possibly adverse role of leptin treatment in nonlipodystrophic patients with nonalcoholic fatty liver disease. In this review, we present a description of leptin biology and signaling; we summarize leptin's contribution to glucose metabolism in animals and humans in vitro, ex vivo, and in vivo; and we provide insights into the emerging clinical applications and therapeutic uses of leptin in humans with lipodystrophy and/or diabetes.
Keywords: Animals; Diabetes Mellitus; HIV-Associated Lipodystrophy Syndrome; Humans; Hypoglycemic Agents; Insulin Resistance; Leptin; Lipodystrophy, Congenital Generalized; Receptors, Leptin; signal transduction